Metal Alloys in Dentistry: An Outdated Material or Required for Oral Rehabilitation? - Matos,Jefferson David Melo de (Universidad de La Frontera. Facultad de Medicina, 2021)
ABSTRACT: The present study aims to describe through a literature review, the main types of noble and non-noble alloys in dentistry looking to identify the adhesion mechanisms, compositions and mechanical properties, and its applicability as a rehabilitation resource nowadays. A bibliographic search was conducted in the main health databases PUBMED (www.pubmed.gov) and Scholar Google (www.scholar.google.com.br), in which studies published from 1971 to 2021 were collected. Laboratory studies, case reports, systematic and literature reviews, which were developed in living individuals. Articles that did not deal with metal alloys and its use in dentistry were excluded. Through the review, it was possible to ver ify that all works presented the metal alloys and their main properties, indicating that they are divided into three main types: hi gh noble alloys, noble alloys and base metal alloys differing in their levels of constituent noble metals. Several alloys and meta ls are available for the dental market each presenting advantages and disadvantages, mainly based on its specific composition.Continuous research and development are resulting in the production of new technologies and products, giving dental surgeons even more options in the design and manufacture of restorations using metal alloys and understanding that these resources will still be viable alternatives in oral rehabilitations. However, further studies on metal alloys are needed to better understand this subject.